A COMPREHENSIVE SYSTEMATIC REVIEW OF THE ASSOCIATION BETWEEN PERIPHERAL ARTERY DISEASE AND CARDIOVASCULAR MORTALITY - Jeffy Marta (International Medical Journal Corp. Ltd, 2026)
Introduction: Peripheral artery disease (PAD) affects more than 230 million people worldwide yet remains under-detected and under-treated relative to coronary and cerebrovascular disease. Although PAD is widely acknowledged to confer cardiovascular (CV) risk, the magnitude, consistency, gradient and modifiability of its association with CV mortality across disease stages, ankle-brachial index (ABI) strata and comorbidity phenotypes have not been comprehensively synthesised. This review quantified that association and determined whether excess CV mortality is amenable to contemporary therapy. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligible designs comprised randomised controlled trials (RCTs) and primary observational studies (prospective/retrospective cohort, case-control, cross-sectional and registry-based) reporting CV or all-cause mortality in adults with PAD or abnormal ABI. Systematic reviews and meta-analyses were excluded from primary tabulation but retained for triangulation. Risk of bias was appraised with Cochrane RoB 2 and Newcastle-Ottawa Scale; certainty was rated with GRADE. Synthesis was narrative with structured tabulation across fifteen prespecified outcome domains. Results: Fifty-four primary studies (13 randomised/trial-derived, 41 observational) encompassing >9 million individuals were included. PAD demonstrated consistent, significant association with CV death. In population-based cohorts, age-adjusted CV mortality hazard ratios (HRs) rose stepwise across disease stage: 1.9 for asymptomatic PAD, 2.6 for intermittent claudication, and 3.5 for severe limb ischaemia; ten-year all-cause mortality rose from 27% in referents to 75% in severe limb ischaemia. Low ABI (≤0.90) approximately doubled to quadrupled CV mortality, while high ABI (>1.40) carried comparable risk, describing a U-shaped hazard. PAD without coronary heart disease or stroke carried prognosis comparable to coronary heart disease or stroke without PAD (adjusted HR 1.68 versus 1.81). Comorbidity markedly amplified risk: concomitant chronic kidney disease and PAD raised cardio-cerebrovascular mortality >4-fold (HR 4.76); critical limb ischaemia in type 2 diabetes raised CV mortality >6-fold (SHR 6.20). Polyvascular involvement produced monotonic risk gradient. Critically, excess risk proved modifiable: low-dose rivaroxaban plus aspirin significantly reduced CV death (HR 0.78) and all-cause death (HR 0.82), reduced MACE composite in PAD (HR 0.72), and reduced major adverse limb events by 43%, while multi-drug secondary prevention was associated with 65% lower all-cause mortality in screen-detected PAD. GRADE certainty was moderate for prognostic domains and high for randomised therapeutic evidence. Discussion: The evidence base demonstrates internal coherence across trial and observational designs, continents and decades. PAD indexes total atherosclerotic burden rather than limb-confined disease, explaining why asymptomatic PAD is nearly as lethal as symptomatic disease, why abnormal ABI predicts death after Framingham adjustment, and why cardiac events dominate mortality. Residual thrombotic risk, systemic inflammation, arterial calcification, renal dysfunction and treatment inequity constitute principal mechanisms. Limitations include heterogeneity of PAD ascertainment, reliance on administrative coding, and probable under-representation of low- and middle-income settings. Conclusion: PAD demonstrates independent, consistent, significant association with CV mortality with reproducible dose-response gradient across haemodynamic severity, symptom stage, vascular-bed burden and comorbidity load. Because excess risk is demonstrably attenuated by intensified antithrombotic therapy and comprehensive risk-factor control, PAD should be treated operationally as coronary risk equivalent, and ABI measurement should be embedded in CV risk stratification. Systematic case-finding coupled with guideline-directed medical therapy represents immediately actionable, evidence-supported strategy for reducing CV death.